Immunoglobulin A1 and A2 subclass of salivary antibodies to Candida albicans in patients with oral candidosis. - Jeganathan, S (1987)
Immunoglobulin A antibody titres to a cytoplasmic protein extract of Candida albicans were determined by ELISA in saliva from 20 patients with oral candidosis and 21 controls. Patients had significantly increased levels of salivary IgA anti-Candida antibodies when compared with controls (P less than 0.001). Antibody levels were associated with IgA1 subclass in 90% of the patients; in contrast, IgA2 subclass was predominant in 67% of the controls. Antifungal therapy resulted in significantly decreased IgA1 titres (P less than 0.05) whilst the mean IgA2 antibody titre remained unchanged. The results indicate that Candida infection may change the subclass pattern of salivary IgA antibodies.